2007
DOI: 10.1021/jm070524a
|View full text |Cite
|
Sign up to set email alerts
|

Identification of New Functional Inhibitors of Acid Sphingomyelinase Using a Structure−Property−Activity Relation Model

Abstract: Some organic weak bases induce a detachment from inner lysosomal membranes and subsequent inactivation of acid sphingomyelinase (ASM) and thus work as functional ASM inhibitors. The aim of the present investigation was to develop a structure-property-activity relation (SPAR) model in order to specify the structural and physicochemical characteristics of probes capable of functionally inhibiting ASM. High p K a and high log P values are necessary but not sufficient preconditions for functional inhibition of ASM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
215
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 209 publications
(222 citation statements)
references
References 111 publications
(175 reference statements)
6
215
0
1
Order By: Relevance
“…1b,c; Supplementary Fig. 1a,b,d, Supplementary note 1), a finding consistent with the induction of partial proteolysis of Asm by amitriptyline and fluoxetine 15,16 . Mice transgenic for Asm (tAsm) exhibited increased Asm activity and protein levels in the hippocampus, and amitriptyline and fluoxetine reduced Asm activity and protein levels ( Fig.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…1b,c; Supplementary Fig. 1a,b,d, Supplementary note 1), a finding consistent with the induction of partial proteolysis of Asm by amitriptyline and fluoxetine 15,16 . Mice transgenic for Asm (tAsm) exhibited increased Asm activity and protein levels in the hippocampus, and amitriptyline and fluoxetine reduced Asm activity and protein levels ( Fig.…”
supporting
confidence: 81%
“…To further substantiate the role of the Asm/ceramide system as a target for antidepressants, we tested whether fendiline, a functional inhibitor of ASM 16 , that has not been reported to be an antidepressant, also acts as antidepressant. Fendiline reduced Asm activity and reduced ceramide concentrations in the hippocampus in WT and t-Asm ( Fig.…”
Section: Gulbins Et Al: Acid Sphingomyelinase and Antidepressant Drumentioning
confidence: 99%
“…Several studies [77-80] identified pharmacological inhibitors of the acid sphingomyelinase; the acid sphingomyelinase seems to interact with intra-lysosomal membranes, thereby being protected against proteolytic inactivation [77]. Weak bases such as amitriptyline diffuse into cells, are protonated in lysosomes and concentrated in these organelles.…”
Section: Sphingomyelinasesmentioning
confidence: 99%
“…Weak bases such as amitriptyline diffuse into cells, are protonated in lysosomes and concentrated in these organelles. High pKa- and high logP-values of the drugs are necessary but not sufficient to functionally inhibit the acid sphingomyelinase [80]. These drugs interfere with binding of the acid sphingomyelinase to the membrane, which results in a detachment of the acid sphingomyelinase and subsequent proteolytic degradation [77-80].…”
Section: Sphingomyelinasesmentioning
confidence: 99%
See 1 more Smart Citation